Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1139/x06-139
|View full text |Cite
|
Sign up to set email alerts
|

Five-year growth responses of Douglas-fir, western hemlock, and western redcedar seedlings to manipulated levels of overstory and understory competition

Abstract: Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco), western hemlock (Tsuga heterophylla (Raf.) Sarg.), and western redcedar (Thuja plicata Donn ex D. Don) seedlings were planted in March 2001 within three clearcut-harvested, shelterwood, or thinned stands of mature Douglas-fir near Olympia, Washington. From 2002 to 2005, areas of vegetation control of 0, 4.5, or 9 m2 were maintained with herbicides around a total 162 seedlings per species. Photosynthetically active radiation (PAR) was 34%, 62%, and 100% of ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 19 publications
6
33
0
1
Order By: Relevance
“…Harrington (2006) found that overstorey density and vegetation control had additive effects on Pseudotsuga menziesii seedling responses and did not interact. However, in a previous study, Groot (1999) observed interactions between overstorey treatment (clearcut versus shelterwood) and vegetation control.…”
mentioning
confidence: 91%
“…Harrington (2006) found that overstorey density and vegetation control had additive effects on Pseudotsuga menziesii seedling responses and did not interact. However, in a previous study, Groot (1999) observed interactions between overstorey treatment (clearcut versus shelterwood) and vegetation control.…”
mentioning
confidence: 91%
“…Given that hybrid poplars have high needs for resources, they are also known to be particularly sensitive to competition (Stanturf et al, 2001;Kabba et al, 2007Kabba et al, , 2009. Competition control generally has positive effects on early development of seedlings because the first few years are the most critical for survival (Morris et al, 1993;Löf, 2000;Harrington, 2006). The control of competing vegetation typically proves beneficial to hybrid poplars (Stanturf et al, 2001), although experimental results may diverge, with some pointing towards effectiveness of the removal of aboveground vegetation only (Czapowskyj and Safford, 1993) while others insist on the need to target belowground plant parts (Coll et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Salal is capable of gaining near complete occupancy of a site (Haeussler et al 1990) and is considered to be a vigorous competitor with trees for water and nutrients (Fraser et al 1993). On dry sites, salal is believed to be a serious competitor for moisture, and several field studies have reported increases in growth and moisture status of Douglas-fir following removal of salal (Kelliher 1985, Vihanek 1985, Price et al 1986, D'Anjou 1998, Harrington 2006. In contrast, Sabhasri (1961) reported that salal removal reduced growth of Douglas-fir in western Washington.…”
Section: Introductionmentioning
confidence: 99%